Curriculum Development, Guidance, and Innovation in Schools - Ulum, Miftachul; Mun'im, Abdul (Journal of Islamic Education, 2023)
The purpose of this research is to explain the purpose of developing, fostering and innovating curriculum. Want to explain the renewal of the school curriculum and the impact of curriculum reform in schools. The research method used is library research starting from collecting research materials to analysis. The results of the research Curriculum development and development activities are activities that alternate or can be said as one cycle, after the development activities are completed, they are continued with coaching activities. Renewal does not by itself bring improvement even though it is intended to improve / improve quality. This depends on the implementation and assessment of the value system is determined. Every curriculum change must have a clear philosophy that underlies it, it also needs intensive outreach to the community